PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VI DI SDN 1 SUKAHURIP - Karim, Yusup Abdul; Hidayat, Yusuf; Purbayani, Rini (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
Critical thinking is a crucial 21st-century skill, especially for helping students solve problems and make sound decisions. This research aimed to explore the implementation of the Pancasila Student Profile Reinforcement Project (P5) in enhancing the critical thinking skills of sixth-grade students at SDN 1 Sukahurip. The P5 project proved effective in boosting the critical thinking skills of these students. This qualitative classroom action research, which adopted Kurt Lewin's Model, involved sixth-grade students in project-based learning. Before P5 implementation, the average critical thinking skill score of students was only 1.8, falling into the